STUDY OF ACUTE BACTERIAL MENINGITIS IN CHILDREN BY GRAM STAIN, CULTURE AND ANTIGEN DETECTION - RAMYASRI, KOSANAM; RAJYALAKSHMI, GUNTI; RANI, ARAVADURGA; DS, MURTHY (International Journal of Current Pharmaceutical Research, 2024)
Objective: Acute Bacterial Meningitis (ABM) is associated with a high mortality rate and morbidity in paediatric population despite recent advances in diagnostic methods, antimicrobial and supportive treatments and monitoring. This study is therefore undertaken to aid in rapid diagnosis of ABM by latex agglutination test (LAT) and to comparatively evaluate Gram stain, Culture and LAT in the diagnosis of ABM along with antibiotic susceptibility pattern of the isolates. We undertake this study in children with symptoms of meningitis to isolate and identify the pathogens in CSF and blood and to determine their antibiotic susceptibility pattern. We will compare and evaluate the three methods Gram stain, culture and Antigen detection. Methods: A hospital-based prospective study conducted at Government General Hospital, Kakinada during December 2018–August 2020. A total of 50 clinically suspected cases of bacterial meningitis in the paediatric age group were taken. The CSF sample was collected and subjected to Gram stain, culture and antigen detection tests using PASTOREX TMMENINGITIS kit. Results: Out of 50 samples collected, 15 cases were declared as laboratory confirmed cases as per WHO criteria. Gram stain was positive in 6 cases. CSF culture could identify 8 cases of ABM. CSF LAT was positive in 12 cases. Group B Streptococcus was the most common etiological agent in neonates, while S. pneumoniae in children. The isolates were 100% sensitive to cefoperazone, cefuroxime, cefepime and gentamicin. Conclusion: Although Gram stain is simple and CSF culture is the gold standard, LAT has an advantage over Gram stain in terms of species identification. It was found to be more sensitive, rapid, easy to perform and could identify fastidious organisms like S. pneumoniae, N. meningitidis and Group B Streptococcus.